Indian government and social policy. Integral Development Program for Yaqui Tribe, Sonora, Mexico - Francisca de la Maza (CUHSO)
The general theme addressed is the contemporary situation of the Yaqui Tribe in northwesternMexico, for their own indigenous forms of government and social policy developed by the Mexican stateand federal governments between 1989 and 2003. During this period we implemented the ComprehensiveDevelopment Plan of the Yaqui tribe based on self-important of the Yaquis with nancial support fromboth the federal and state government. From this, we analyze some descriptive elements of indigenousorganizational aspect of Mexican social policy from a theoretical perspective that accounts for differentsituations. Particularly Yaqui political practice within the framework of ethnicity, namely the constructionof this practice over time through the relationship with the Mexican government and other external agentsunder a complex system of domination, including political, economic, social and cultural, that make up acurrent scenario of mutual influence and dependence.